2003
DOI: 10.1016/s0375-9601(03)00448-1
|View full text |Cite
|
Sign up to set email alerts
|

BBGKY hierarchy underlying many-particle quantum mechanics

Abstract: Recently, the one particle quantum mechanics has been obtained in the framework of an entirely classical subquantum kinetics. In the present paper we argue that, within the same scheme and without any additional assumption, it is possible to obtain also the n-particle non relativistic quantum mechanics. The main goal of the present effort is to show that the classical BBGKY hierarchical equation, for the n-particle reduced distribution function, is the ancestor of the n-particle Schrödinger equation. On the ot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The theory of the BBGKY hierarchy is developing now since the area of its application grows [14,15]. At present while solving the initial value problem of the BBGKY hierarchy, many mathematical problems arise [3,5,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…The theory of the BBGKY hierarchy is developing now since the area of its application grows [14,15]. At present while solving the initial value problem of the BBGKY hierarchy, many mathematical problems arise [3,5,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…[131,132,133] -see also e.g. [67,70,86,119,120,121]) and sketch some formulas for a simple Euclidean metric where ∆ = (∂/∂x i ) 2 . Then ψ(t, x) = exp[R(t, x) + iS(t, x)] satisfies a SE i∂ t ψ + (1/2)∆ψ + ia(t, x) · ∇ψ − V (t, x)ψ = 0 ( = m = 1)) if and only if where the creation and annihilation term c(t, x, φ) is given via…”
Section: The Schrödinger Equationmentioning
confidence: 99%
“…Bogoliubov and Kraeft et al [3] [4] defined a set of equations describing the dynamics of a system of a large number of interacting par-International Journal of Astronomy and Astrophysics ticles by using the quantum BBGKY hierarchy. Kaniadakis [5] showed that the classical BBGKY hierarchical equation, for the n-particle reduced distribution function. Fesciyan [6] calculated the quantum time independent BBGKY hierarchy of equations at low densities.…”
Section: Introductionmentioning
confidence: 99%